2022
DOI: 10.1155/2022/7954589
|View full text |Cite|
|
Sign up to set email alerts
|

Application of Support Vector Machine Model Based on Machine Learning in Art Teaching

Abstract: The purpose of the evaluation is to reflect on whether education provides a good environment and conditions for the development of students and to reflect on the effect of teaching and the practicability of the talents cultivated by teaching to the society. When art education is evaluated, a number of positive outcomes have been achieved in terms of the development of art education, including the improvement of art education as a whole, the development of art talent, and a stronger role for the educational and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The SVM is a classification method that effectively reduces model complexity while accurately fitting the training data. The approach operates by identifying linear hyperplanes that maximize the distance between two sides or edges of several hyperplanes, thereby minimizing the likelihood of generalization errors [ 41 ]. Reducing the number of support vectors (data point closest to the hyperplane), helps to simplify the model and reduce overfitting.…”
Section: Methodsmentioning
confidence: 99%
“…The SVM is a classification method that effectively reduces model complexity while accurately fitting the training data. The approach operates by identifying linear hyperplanes that maximize the distance between two sides or edges of several hyperplanes, thereby minimizing the likelihood of generalization errors [ 41 ]. Reducing the number of support vectors (data point closest to the hyperplane), helps to simplify the model and reduce overfitting.…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated that the proposed strategy provides more accurate learning improvement than the current method. The existing methodologies like CNN [23], SVM [24] and KNN [25]. With the suggested system, accuracy is at 93%, while CNN is at 75%, SVM is at 63%, and KNN is at 82%.…”
Section: Accuracymentioning
confidence: 96%
“…The article developed the strength of the social and educational sectors involved with the standard of art education, as well as artistic potential. The article based on machine learning may more successfully address problems including nonlinearity, high dimensionality, and local minima [24].The overview's goal is to determine accurate the classification of "Chinese Bridge" learners, a classification approach based on the enhanced K-Neighbor Algorithm has been proposed. It is integrated with the theory of the internal factor evaluation matrix.…”
Section: Introductionmentioning
confidence: 99%
“…First, it is used to study DL computing techniques and the modelling art education platform. Secondly, art teaching platform looks into then evaluates daily learning status of students as well as the teaching strategies used in schools [21][22][23][24][25][26][27].…”
Section: A Problem Statement and Motivation Behind This Research Workmentioning
confidence: 99%